Kinerja Guru Sekolah Dasar di Kabupaten Muna, Provinsi Sulawesi Tenggara - Mutu, La (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study investigates how principal supervision and teacher work motivation influence teacher performance. Utilizing path analysis, data from 88 teachers were assessed after integrating all variables into the covariance matrix. The analysis yielded several significant relationships: (1) principal supervision has a direct effect on teacher performance, contributing 33.9% (coefficient = 0.339); (2) work motivation directly impacts teacher performance at a rate of 43.8% (coefficient = 0.438); (3) principal supervision significantly affects work motivation with a direct contribution of 66.7% (coefficient = 0.667); and (4) principal supervision also exerts an indirect effect on teacher performance mediated by work motivation, as evidenced by a Sobel test score of 2.6157 and a t-statistic of 4.617, surpassing the critical t-value of 1.989. These findings suggest that enhancements in teacher performance are significantly driven by effective leadership from principals and the strengthening of teacher motivation. Therefore, both elements should be prioritized in strategies aimed at improving educator effectiveness in public elementary schools throughout Muna Regency.